PENINGKATAKAN KETERAMPILAN MENULIS CERITA PENDEK MENGGUNAKAN MODEL AUDIOTORY, INTELLECTUALLY, REPETITION PADA SISWA KELAS V SEKOLAH DASAR 020 RIDAN PERMAI - Dhea Juniati Riska; Iis Aprinawati; Afriza Rahma Rani; Mufarizuddin; Yenni Fitra Surya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the low short story writing skills of students in Indonesian language lessons in fifth grade. The aim of this research is to improve the short story writing skills of fifth-grade students at UPT Sekolah Dasar Negeri 020 Ridan Permai. The subjects consisted of 25 students, comprising 11 male and 14 female students. This research uses a Classroom Action Research (CAR) method, conducted in two cycles. Each cycle consisted of two meetings and four stages: planning, implementation, observation, and reflection. The research was conducted from Wednesday, May 21, 2025, to May 28, 2025. Data collection techniques included documentation, observation, and tests. Based on the data analysis results, there was an improvement in short story writing skills in the Indonesian language subject. The initial pre-action classical completeness was 32.06%, in Cycle I Meeting I it increased to 38.42%, then to 44.81% in Meeting II. In Cycle II Meeting I, it rose significantly to 86.43%, and further increased to 91.21% in Cycle II Meeting II. Therefore, it can be concluded that the Auditory, Intellectually, Repetition learning model can improve the short story writing skills of fifth-grade students at UPT SDN 020 Ridan Permai. Keywords: Short Story Writing Skills, Auditory, Intellectually, Repetition